Long‐term BP control and vascular health in patients with hyperaldosteronism treated with low‐dose, amiloride‐based therapy. Issue 7 (6th June 2019) - Izzo, Joseph L.; Hong, Michael; Hussain, Tanveer; Osmond, Peter J.
Abstract: Whether aldosterone itself contributes directly to macro‐ or microcirculatory disease in man or to adverse cardiovascular outcomes is not fully known. We report our long‐term single‐practice experience in 5 patients with chronic hyperaldosteronism (HA, including 3 with glucocorticoid remediable aldosteronism, GRA) treated with low‐dose amiloride (a specific epithelial sodium channel [ENaC] blocker) 5‐10 (mean 7) mg daily for 14‐28 (mean 20) years. Except for 1 GRA diagnosed in infancy, all had severe resistant hypertension. In each case, BP was normal or near‐normal within 1‐4 weeks after starting amiloride and office BP's were well controlled for 20 years thereafter. Vascular studies and 24‐hour ambulatory BP monitoring with pulse wave analysis (cardiac output, vascular resistance, augmentation index, and reflection magnitude) were assessed after a mean of 18 years as were regional pulse wave velocities, pulse stiffening ratio, ankle‐brachial index, serum creatinine, estimated glomerular filtration rate, and spot urinary albumin:creatinine ratio. All indicators were completely normal in all patients after 18 years of amiloride, and none had a cardiovascular event during the 20‐year mean follow‐up. We conclude that long‐term ENaC blockade can normalize BP and protect macro‐ and microvascular function in patients with HA. This suggests that (a) any vasculopathic effects of aldosterone are mediated via ENaC, not MR activation itself, and are fully preventable or reversible with ENaC blockade or (b) aldosterone may not play a major BP‐independent role in human macro‐ and microcirculatory diseases. These and other widely divergent results in the literature underscore the need for additional studies regarding aldosterone, ENaC, and vascular disease.